Theoretical B3LYP Study on Electronic Structure of Contrast Agent Iopamidol - Fatma Genç; Sedat Giray Kandemirli; Fatma Kandemirli (Slovenian Chemical Society, 2021)
Nonionic low-osmolar contrast agents are thought about safe for intravenous or intra-arterial administration. Iopamidol is one of the contrast agents used for diagnostic clinical computed tomography (CT) protocols last four decades years. The molecular structure of Iopamidol was calculated by the B3LYP density functional model with the LANL2DZ basis set by the Gaussian program. The natural bond orbital analysis in terms of the hybridization of atoms and the electronic structure of the title molecule have been analyzed by using the data obtained from the quantum chemical results. First-order hyperpolarizability (βtot), the dipole moment (μ) and polarizability (α) and anisotropic polarizability (Δα) of the molecule have been reported. HOMO and LUMO energies and parameters related to energies, and dipole moment, polarizability and hyperpolarizability show minor dependences on the solvent polarity. The hardness of Iopamidol decreases with increasing solvent polarity. The stability of the Iopamidol contrast agent with the hyper conjugative interactions, charge delocalization has been analyzed using natural bond orbital analysis. In addition, thermodynamic properties were obtained in the range of 200–1000 K.
Keywords: b3lyp; electronic structure.; Molecular Structure; gaussian program; Contrast Media; Electrons; dft; Iopamidol; Chemistry; Thermodynamics; quantum chemical calculations; iopamidol; QD1-999; Density Functional Theory